Democratizing artificial intelligence with UiPath - Ip, Fanny; Crowley, Jeremiah (Packt Publishing, 2022)
Build an end-to-end business solution in the cognitive automation lifecycle and explore UiPath Document Understanding, UiPath AI Center, and Druid Key Features Explore out-of-the-box (OOTB) AI Models in UiPath Learn how to deploy, manage, and continuously improve machine learning models using UiPath AI Center Deploy UiPath-integrated chatbots and master UiPath Document Understanding Book Description Artificial intelligence (AI) enables enterprises to optimize business processes that are probabilistic, highly variable, and require cognitive abilities with unstructured data. Many believe there is a steep learning curve with AI, however, the goal of our book is to lower the barrier to using AI. This practical guide to AI with UiPath will help RPA developers and tech-savvy business users learn how to incorporate cognitive abilities into business process optimization. With the hands-on approach of this book, you'll quickly be on your way to implementing cognitive automation to solve everyday business problems. Complete with step-by-step explanations of essential concepts, practical examples, and self-assessment questions, this book will help you understand the power of AI and give you an overview of the relevant out-of-the-box models. You'll learn about cognitive AI in the context of RPA, the basics of machine learning, and how to apply cognitive automation within the development lifecycle. You'll then put your skills to test by building three use cases with UiPath Document Understanding, UiPath AI Center, and Druid. By the end of this AI book, you'll be able to build UiPath automations with the cognitive capabilities of intelligent document processing, machine learning, and chatbots, while understanding the development lifecycle. What you will learn Discover how to bridge the gap between RPA and cognitive automation Understand how to configure, deploy, and maintain ML models in UiPath Explore OOTB models to manage documents, chats, emails, and more Prepare test data and test cases for user acceptance testing (UAT) Build a UiPath automation to act upon Druid responses Find out how to connect custom models to RPA Who this book is for AI Engineers and RPA developers who want to upskill and deploy out-of-the-box models using UiPath's AI capabilities will find this guide useful. A basic understanding of robotic process automation and machine learning will be beneficial but not mandatory to get started with this UiPath book.